2020
DOI: 10.34172/ps.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Condensate: A Non-Invasive Source for Tracking of Genetic and Epigenetic Alterations in Lung Diseases

Abstract: Lung diseases have been recognized as an extensive cause of morbidity and mortality in the worldwide. The high degree of clinical heterogeneity and nonspecific initial symptoms of lung diseases contribute to a delayed diagnosis. So, the molecular and genomic profiling play a pivotal role in promoting the pulmonary diseases. Exhaled breath condensate (EBC) as a novel and potential method for sampling the respiratory epithelial lining fluid is to assess the inflammatory and oxidative stress biomarkers, drugs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 120 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…Also, to evaluate the effect of AgNPrs and MDA in the real sample, a healthy urine sample was used without any pretreatment. 53 …”
Section: Methodsmentioning
confidence: 99%
“…Also, to evaluate the effect of AgNPrs and MDA in the real sample, a healthy urine sample was used without any pretreatment. 53 …”
Section: Methodsmentioning
confidence: 99%
“…Exhaled breath (EB) analysis, a non-invasive and simple method, has been utilized in the diagnosis and investigation of some conditions such as kidney problems, diabetes, and lung-related diseases. 1,2 Recent studies confirmed that EB can also be utilized for pharmacological studies. [3][4][5][6] Generally, the development of a sensing platform in common biological media like plasma, serum, blood, etc.…”
Section: Introductionmentioning
confidence: 97%